2023
DOI: 10.1002/eem2.12467
|View full text |Cite
|
Sign up to set email alerts
|

CoS2/S‐Doped C with In Situ Constructing Heterojunction Structure for Boosted K‐Ion Diffusion and Highly Efficient Storage

Abstract: Exploring the desired anode materials to address the issues of poor structural stability tardy redox kinetics caused by large potassium ionic radius are fatal for the realization of large‐scale applications of potassium‐ion batteries. In this work, the feasibility to achieve promoted K+ storage by constructing the model of CoS2 enfolded in carbon was verified by the density functional theory calculations. And the results predicted a faster electron/potassium ion transport kinetics than bare CoS2 by increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Through combining the EIS test with variable temperature, it is possible to measure the impedance activation energy of each electrochemical process in the graphite electrode. Assuming that the charge transfer resistance is a simple thermally activated process, the sensitivity of different electrochemical impedance to temperature can be speculated by following equation 37,[42][43][44][45] R R 1 e 5…”
Section: Description Of Solid-state LI + Diffusion Coefficient Testmentioning
confidence: 99%
“…Through combining the EIS test with variable temperature, it is possible to measure the impedance activation energy of each electrochemical process in the graphite electrode. Assuming that the charge transfer resistance is a simple thermally activated process, the sensitivity of different electrochemical impedance to temperature can be speculated by following equation 37,[42][43][44][45] R R 1 e 5…”
Section: Description Of Solid-state LI + Diffusion Coefficient Testmentioning
confidence: 99%
“…It is found that the E b for path-1 (0.19 eV) is much lower than for path-2 (0.31 eV), confirming that the MEP of K atom within the interlayer of SnS 2 is along a curved zigzag direction alternating between O h and T d sites. We have compared the Kion diffusion barrier in SnS 2 to several typical anode materials with similar crystal structure, including MoS 2 (0.19 eV), 62 CoSe 2 (0.30 eV), 63 CoS 2 (0.27 eV), 64 and NiS 2 (0.20 eV). 65 These results clearly demonstrate the facile diffusivity of K ions in the interlayers of SnS 2 .…”
Section: Intercalation and Diffusion Of K In Snsmentioning
confidence: 99%
“…[5][6][7][8][9] In this case, potassium-ion batteries (PIBs) are one of the most promising candidates especially for future large-scale energy storage, since potassium offers cheaper cost (17 000 ppm for K vs 20 ppm for Li) and higher natural resource reserves (1.5 wt% of K vs 0.0017 wt% of Li). [10][11][12] Furthermore, PIBs with comparable K/K + redox potential (−2.93 V vs standard hydrogen electrode [SHE]) to Li/Li + (−3.04 V vs SHE) and smaller Stokes radius of solvated K + (3.6 Å for K + vs 4.8 Å for Li + ) have attracted great attention for large-scale applications. [13][14][15][16] However, it is generally recognized that the practical application of PIBs is hindered by the low power density and inferior cycling stability.…”
Section: Introductionmentioning
confidence: 99%